Work time demand and job satisfaction of geographically dispersed team: The mediating role of organizational support - Yong, Shee-Mun; Thi, Lip Sam (2015)
Employee job satisfaction is often attributed to amongst others the level of co-worker and supervisory support in an organization.For geographically dispersed teams (GDT), the ability to support team members remains a spatiotemporal challenge with limited face-to-face contact, time zone differences, cultural and language impediments.The inability to collaborating and organizing work across different time zones with few overlapping hours exert psychosocial stress that impedes job satisfaction.This research was undertaken to gauge the satisfaction level of Malaysian GDTs working under such conditions and the effect of organizational support to buffer the impact and restore job satisfaction. Outcome of the quantitative survey involving 306 Information Technology Outsourcing and Business Processing Outsourcing respondents located in multimedia-super corridor flagship town of Cyberjaya shows a causal linkage between work time demand and job satisfaction. The finding also reveals that job satisfaction is partially mediated by organizational support in relation with work time demand.